Prolonged Continuous Theta Burst Stimulation of the Motor Cortex Modulates Cortical Excitability But not Pain Perception - Klírová, Monika; Hejzlar, Martin; Kostýlková, Lenka; Mohr, Pavel; Rokyta, Richard; Novák, Tomáš (Frontiers in Systems Neuroscience, 2020)
Over the past decade, theta burst stimulation (TBS) has become a focus of interest in neurostimulatory research. Compared to conventional repetitive transcranial magnetic stimulation, TBS produces more robust changes in cortical excitability (CE). There is also some evidence of an analgesic effect of the method. Previously published studies have suggested that different TBS parameters elicit opposite effects of TBS on CE. While intermittent TBS (iTBS) facilitates CE, continuous TBS (cTBS) attenuates it. However, prolonged TBS (pTBS) with twice the number of stimuli produces the opposite effect. In a double-blind, placebo-controlled, cross-over study with healthy subjects (n=24), we investigated the effects of various pTBS (cTBS, iTBS, and placebo TBS) over the right motor cortex on CE and pain perception. Changes in resting motor thresholds (RMT) and absolute motor-evoked potential (MEP) amplitudes were assessed before and at two time points (0-5 minutes; 40-45 minutes) after pTBS. Tactile and thermal pain thresholds were measured before and 5 minutes after application. Compared to the placebo, prolonged cTBS (pcTBS) transiently increased MEP amplitudes, while no significant changes were found after prolonged iTBS. However, the facilitation of CE after pcTBS did not induce a parallel analgesic effect. We confirmed that pcTBS with twice the duration converts the conventional inhibitory effect into a facilitatory one. Despite the short-term boost of CE following pcTBS, a corresponding analgesic effect was not demonstrated. Therefore, the results indicate a more complex regulation of pain, which cannot be explained entirely by the modulation of excitability.